Assessing national action plans on antimicrobial resistance in animal production What lessons can be drawn? - Ryan, Michael (OECD Food, Agriculture and Fisheries Papers, 2021)
Global efforts to combat the risks posed by antimicrobial resistance (AMR) depend on effective implementation of national action plans. Most countries have taken a One Health approach in developing their national action plans covering human health, animal health and the environment. Evidence on the implementation of these plans in livestock agriculture across six OECD countries, as well as in Brazil, the People's Republic of China, and the Russian Federation, highlights the need for greater co-ordination and coherence amongst stakeholders in implementing workable solutions. This includes developing integrated surveillance and monitoring systems, improving regulations on the availability of antibiotics, and improving on-farm biosecurity practices. Additional efforts to enhance public awareness, to improve education and training, and to explore alternative interventions and innovations to antimicrobials in animal health and animal welfare could also improve outcomes in this area. The lack of long-term funding continues to hinder the implementation of national action plans on AMR.